AS LIDERANÇAS TERENA E OS DESAFIOS ENFRENTADOS NAS ALDEIAS URBANAS DE CAMPO GRANDE-MS - ELIDIO VICENTE PEREIRA NETO (2024)
ABSTRACT When we conduct research related to indigenous peoples and their challenges in an urban context, we open up a range of possibilities and issues to be debated. In the case of Terena leaders in Campo Grande/MS, the challenges have in fact been occurring for some decades and several issues are discussed by some authors. This work aims to bring to light some considerations pertaining to the politics of Terena leaders in the context of Campo Grande/MS, such as the actions of Terena leaders in the urban villages of the city and how they deal with both the villages they lead and the non-indigenous population of the city. The importance of this issue lies precisely in the text's listing of the adaptability of the Terena peoples, from occupations to the search for a better quality of life, such as professional qualifications and studies. In the first chapters, we seek to provide a brief historical contextualization of the Terena peoples in the region that is now the state of Mato Grosso do Sul. We then relate, with Clastres (2003), the ways in which South American indigenous people conduct themselves politically (or not). In chapter 3, we carried out our long-awaited field work seeking out indigenous leaders from urban villages in Campo Grande/MS and interviewing them, always seeking out the different ways these leaders deal with their subordinates. Keywords: Terena Leadership, Urban Villages, Adaptability and Policies.